The Authority of the Accounting Principles Board. - Kemp, Patrick S. (The Accounting Review, 1965)
The purpose of this paper is to examine the progress made by the Accounting Principles Board in attempting to solve the reporting problems of the accounting profession, up to and including the American Institute of Certified Public Accountant (AICPA) Council action noted above and to speculate upon the future status of the profession. In order to put the problem in perspective, the origins and history of the Accounting Principles Board are briefly presented. Then, certain implications of the October, 1964, AICPA Council action are discussed. Finally, some speculations are advanced concerning necessary steps to be taken in the future. The Accounting Principles Board had its origins in the report of a Special Committee on Research Program of the AICPA, rendered in September 1958 and unanimously adopted by the AICPA Council in April 1959. This committee was appointed in December 1957 to consider a new approach to the means whereby accounting research should be undertaken, accounting principles should be promulgated and adherence to them should be secured.